(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
In present work, Cicer arietinum amylase was encapsulated by emulsification through covalent coupling by glutaraldehyde into chemically modified bovine serum albumin. Biodegradation of coconut oil driven emulsified bovine serum albumin encapsulated Cicer arietinum amylase was carried out by the alkaline protease for its controlled and sustained release of encapsulated enzyme from prepared microparticles of encapsulated Cicer arietinum amylase and its stability increased up to 6 months as compared to free enzyme. Its biodegradation was carried out by the using different concentration of alkaline protease (5U, 10U, 15U, 20U, 25U, 30U, 35U, 40U). Further, this coconut oil driven chemically modified bovine serum albumin microparticles of encapsulated Cicer arietinum amylase with alkaline protease were used with detergents for washing of stained cloths which have rust, gel pen ink, grease and chocolate strains. These chosen strains are very commonly present on uniforms of school going children which are very tough upon drying, hence, not to be easily vanish with well known brand detergents upon in one wash. But, the mixture solution of coconut oil driven chemically modified bovine serum albumin microparticles of encapsulated Cicer arietinum amylase along with alkaline protease were used with detergents powder for washing of these dry tough strains (rust, gel pen ink, grease and chocolate strains) leads to vanishing these strains very fast with absolute clear results were found as compared to results of washing of stained cloths with detergents only.